PELAKSANAAN LATIHAN ARTIKULASI BAGI SISWA TUNARUNGU - Ari - Gusman (Universitas Negeri Padang, 2013)
Background research was conducted because of the constraints experienced articulation teacher in providing articulation training for Deaf students in SLB Negeri 01 Padang. It is caused due to lack of teacher training in the articulation. Besides the lack of special experts provide articulation exercises. Currently implementing articulation exercises in SLB 01 Padang implemented by the class teacher concerned. Based on this background, this study aims to gain an overview of the implementation of articulation training for deaf students in SLB Negeri 01 Padang, in terms of planning, implementation, evaluation, constraints, and effort that seeks to overcome these obstacles. This study used a qualitative descriptive method. Subjects were articulation teachers, students, principals, classroom teachers and parents. Techniques of collecting data used were observation, interview and documentation. Then the data will be described with words or phrases that are separated by category for the conclusion.